Photochemical and antioxidative responses of the glume and flag leaf to seasonal senescence in wheat - Kong, Lingan; Sun, Mingze; Xie, Yan; Wang, Fahong; Zhao, Zhendong (Frontiers in Plant Science, 2015)
The non-leaf photosynthetic organs have recently attracted much attention for the breeding and screening of varieties of cereal crops to achieve a high grain yield. However, the glume photosynthetic characteristics and responses to high temperature at the late stages of grain filling are not well known in winter wheat (Triticum aestivum L.). In the present study, an experiment was conducted to investigate the anatomy, chloroplast temporal changes, chlorophyll fluorescence, xanthophyll cycle and antioxidative defense system in glumes of field-grown wheat during grain filling compared with flag leaves. Observations using a light microscope revealed that the glumes developed a solid structural base for performing photosynthesis. Compared with the flag leaves, the glumes preserved a more integral ultrastructure, as observed under transmission electron microscopy, and had higher values of Fv/Fm and ΦPSII at the maturity stage. Further analysis of the chlorophyll fluorescence demonstrated that the glumes experienced high non-photochemical quenching (NPQ) at the late stages. Determination of the pool size of the xanthophyll cycle suggested that the (A+Z)/(V+A+Z) ratio was consistently higher in glumes than in flag leaves and that the V+A+Z content was considerably higher in glumes at the maturity stage. In addition, the glumes exhibited a higher antioxidant enzyme activity and a lower accumulation of reactive oxygen species. These results suggest that the glumes are photosynthetically active and senesce later than the flag leaves; the advantages may have been achieved by coordinated contributions of the structural features, higher NPQ levels, greater de-epoxidation of the xanthophyll cycle components and antioxidative defense metabolism.